Tracing the sources of bioaccessible metal(loid)s in urban environments: A multidisciplinary approach - Kelepertzis, Efstratios; Chrastný, Vladislav; Botsou, Fotini; Sigala, Evangelia; Kypritidou, Zacharenia; Komárek, Michael; Skordas, Konstantinos; Argyraki, Ariadne (The Science of the total environment, 2021)
Understanding the links between sources of magnetic particles and bioaccessibility of metal(loids) in environmental sampling media is crucial for better evaluating human health risks, although relevant information in the scientific literature is scarce. Here, soil, road and house dust samples from a heavy industrial area in Greece were characterized in a multidisciplinary study combining magnetic measurements, SEM/EDS analyses, bioaccessibility measurements and Pb isotopic analyses of bioaccessible Pb. The oral and inhalable bioaccessible fractions of As, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn were assessed by applying simulated gastric and lung solutions. SEM/EDS analysis revealed the abundant presence of anthropogenic Fe-containing spherules of industrial origin in all sampling media, often containing minor contents of Cr, Cu, Mn, Pb and Zn. The inhalation bioaccessibility (%) in all environmental compartments was higher than the oral one for most elements analyzed in the present study. Clear associations between magnetic susceptibility and bioaccessible amounts of most of analyzed elements were encountered for the soil and road dust. The isotopic analyses of bioaccessible Pb showed that there are significant differences in the isotopic ratios between total and bioaccessible Pb. We conclude that Pb solubilized by the simulated gastric and lung extractions is principally anthropogenic, representing a mixture of industrial Pb and Pb related to the past usage of leaded petrol. Low values of 206Pb/207Pb were accompanied by high bioaccessible contents of Cd, Pb and Zn indicating that anthropogenic (mostly industrial) sources exert influence on the bioaccessible forms of these metals. Coupling magnetic and bioaccessibility measurements with stable isotopic technique of bioaccessible Pb is more reliable for determining Pb and other metal sources with high oral and inhalation bioaccessibility.
Keywords: Metals, Heavy; prach; Dust; Humans; Environmental Monitoring; Soil Pollutants; látky znečišťující půdu; půda; lidé; Road dust; Cities; monitorování životního prostředí; Řecko; těžké kovy; Greece; Metal bioaccessibility; House dust; Risk Assessment; Soil; velkoměsta; Urban geochemistry; hodnocení rizik; Lead isotopes